EVALUASI KEBIJAKAN FOOD ESTATE DI SUMBA TENGAH(Studi Kasus Pengembangan Food Estate di Desa Umbu Pabal dan Desa Wairasa) - Triseven Umbu Ngailu; Boli Tonda Baso; Yonathan h. L Lopo (SINERGI : Jurnal Riset Ilmiah, 2026)
This research is entitled "Evaluation of Food Estate Policy in Central Sumba (Case Study of Food Estate Development in Umbu Pabal and Wairasa Villages). The purpose of this study is to analyze the implementation of the food estate policy in Umbu Pabal and Wairasa Villages, Central Sumba Regency. The theory used in this study is the policy implementation by Merilee S. Grindle. This study employed qualitative research methods, with data collection methods including observation, interviews, and documentation. Based on the results of this study, the implementation of this program has experienced complex and diverse dynamics in various aspects. Overall, this program has had a positive impact on both villages, but with varying degrees of success depending on the local context and implementation approach. From a policy content analysis perspective, the Food Estate program has undergone a significant transformation from a centralized approach to a more participatory model in terms of the interests affected.